The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1063/1.3660284
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen rich p-type ZnO thin films using wet chemical route with enhanced carrier concentration by temperature-dependent tuning of acceptor defects

Abstract: This paper reports the temperature-dependent tailoring of acceptor defects in oxygen rich ZnO thin films, for enhanced p-type conductivity. The oxygen rich p-type ZnO thin films were successfully grown by pulsed laser deposition on silicon substrate at different postdeposition annealing temperatures (500-800 C). The oxygen rich ZnO powder was synthesized by wet chemical method using zinc acetate dihydrate [Zn(CH 3 COO) 2 Á2H 2 O] and potassium hydroxide (KOH) as precursors. The powder was then compressed and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 32 publications
(35 reference statements)
6
43
0
Order By: Relevance
“…4 shows the XPS survey scan of the ZnO thin films at different thickness. In addition to the Zinc (Zn) and Oxygen (O) there is also an evidence for the presence of carbon which may be considered as an impurity during the transfer of samples from ALD to XPS chamber [35,36]. Fig.…”
Section: Xps Surface and Chemical State Analysismentioning
confidence: 99%
“…4 shows the XPS survey scan of the ZnO thin films at different thickness. In addition to the Zinc (Zn) and Oxygen (O) there is also an evidence for the presence of carbon which may be considered as an impurity during the transfer of samples from ALD to XPS chamber [35,36]. Fig.…”
Section: Xps Surface and Chemical State Analysismentioning
confidence: 99%
“…Pelletized PLD targets of ZnO:Mn (with 5% Mn concentration) were synthesized through wet chemical method with the processing conditions reported elsewhere [10][11][12] in our previous studies. The PLD chamber was evacuated to a base pressure of the order of ~10 -6 mbar prior to thin film deposition.…”
Section: Experimentationmentioning
confidence: 99%
“…Sanchez et al have reported that the uncompensated surface spins enhance the spin polarization induced by substitute Ni ions and even in the absence of magnetic ions, it might promote the formation of pderived extended magnetic states [54]. Further, presence of O i , in our samples is favorable to exhibit presence of holes due to the activation of acceptor states [40]. The activation of acceptor states for hole formation might be partly responsible for the enhancement in HTFM in the Ni doped ZnO NRs, also it is consistent with the Dietl's prediction of hole mediated ferromagnetism in Mn doped ZnO system [1].…”
Section: Possible Origin Of the Fm Interactionmentioning
confidence: 69%
“…Next an intense yellow emission (Peak IV) is observed from all of the samples, centered on~2.05 eV. This emission peak may be attributed to the recombination process associated with the ionized oxygen interstitials (O i ) induced transitions [35,40]. Most of the theoretical calculations agree that Zn V and O V are the lowest energy defects, while the Zn i, O i are to be higher in energy.…”
Section: Optical Propertiesmentioning
confidence: 77%